2010
DOI: 10.1186/1758-5996-2-70
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in glucometabolic disorders: an update

Abstract: Many trace elements, among which metals, are indispensable for proper functioning of a myriad of biochemical reactions, more particularly as enzyme cofactors. This is particularly true for the vast set of processes involved in regulation of glucose homeostasis, being it in glucose metabolism itself or in hormonal control, especially insulin. The role and importance of trace elements such as chromium, zinc, selenium, lithium and vanadium are much less evident and subjected to chronic debate. This review updates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 173 publications
(194 reference statements)
5
86
0
7
Order By: Relevance
“…Numerous studies have demonstrated that trace element as zinc, copper, chromium, magnesium, selenium and molybdenum have essential role in insulin action and carbohydrate metabolism. 11 In our study, serum zinc level was significantly lower in diabetic patients (with complications and without complications) compared to the healthy control group, which is in line with the findings of Puri M et al, 2 Olaniyan OO et al, 3 Devi TR et al 4 and Supriya MS et al 5 Zinc is essential for the correct processing, storage, secretion, and action of insulin in beta (β)-cells of pancreas. Insulin is stored inside secretory vesicles or granules.…”
Section: Discussionsupporting
confidence: 80%
“…Numerous studies have demonstrated that trace element as zinc, copper, chromium, magnesium, selenium and molybdenum have essential role in insulin action and carbohydrate metabolism. 11 In our study, serum zinc level was significantly lower in diabetic patients (with complications and without complications) compared to the healthy control group, which is in line with the findings of Puri M et al, 2 Olaniyan OO et al, 3 Devi TR et al 4 and Supriya MS et al 5 Zinc is essential for the correct processing, storage, secretion, and action of insulin in beta (β)-cells of pancreas. Insulin is stored inside secretory vesicles or granules.…”
Section: Discussionsupporting
confidence: 80%
“…So, the reciprocal antagonism between Cu and Fe might be the reason for the increased Fe in the tartrazinetreated rats. Zn is a remarkable antioxidant [32], whose deficiency results in oxidative stress. Oxidative stress due to excessive production of ROS, impaired antioxidant defense mechanisms or both participate in the damage of testicular structure or the architecture of seminiferous tubules, which are believed to negatively affect the male reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experimental studies shown selenate stimulate glucose uptake and involved phosphorylation of insulin receptor and insulin receptor substrate 1 [39,40] and the oral administration or intraperitoneal injection of daily doses of selenate for 3-8 weeks in streptozotocininduced diabetic rat, the result shown that the raised glucose level to be reduced [41,42].…”
Section: Rajendiran Et Almentioning
confidence: 99%